[Horizon Scanning Of Therapeutic Alternatives For Generalized Myasthenia Gravis And Five-Year Healthcare Expenditure Forecast Model] - Silvia Adami; Paolo Emilio Alboni; Adriano Cristinziano; Concetta La Seta; Andrea Marinozzi; Emanuele Colalillo; Rossella Bitonti (Farmeconomia: Health Economics and Therapeutic Pathways)
OBJECTIVE: The objective of the analysis was to assess and quantify the economic impact of generalized Myasthenia Gravis (gMG) in Italy over the next five years (2025—2029) using Horizon Scanning and expenditure forecasting methodologies.